Analisis Budaya Organisasi dan Budaya Keselamatan Pasien Sebagai Langkah Pengembangan Keselamatan Pasien di RSIA Budi Kemuliaan Tahun 2014 - Iriviranty, Afrisya (UI Scholars Hub, 2015)
Establishing patient safety culture is the first step in patient safety improvement.Therefore we need an assessment of patient safety culture in hospitals. Patient safety culture is part of the organizational culture, so that the study of organizational culture needed to be a guidance in developing patient safety. The aims of this study is to determine the patient safety culture among clinical staff in RSIA Budi Kemuliaan and identify organizational culture profiles. This study is descriptive with qualitative interpretation and analysis. It was found that teamwork within the unit is the strongest dimension of patient safety culture. While staffing and non-punitive response is the weakest dimension. Clan culture is the type of the current organizational culture which is dominant and considered as a stong culture. This type is also the preferred culture that are serve as a guide to make changes in the organization, especially in the development of patient safety. Plan of action was made by Consensus Decision Making Group and achieved the agreement to articulating patient safety in the vision and mission of the organization and strengthening safety culture through patient safety training for all staf.